How math shapes the world of life science animation - Oliveira, Rafael; Dias, Evellyn Araujo; Santos, Ricardo; Cotta-De-Almeida, Vinicius; Aguiar Coelho Nt, José; Alves, Luiz Anastácio (Frontiers in Computer Science, 2025)
With the advances in technology, it is noticeable the educational potential of animation in the field of cell biology, physiology and other basic life science disciplines, revolutionizing the learning process in science. This paper elucidates the role of matrix manipulation in animating figures on screens, elucidates the distinctions between Scalable Vector Graphics (SVG), bitmap and raster images, and unveils the inner workings of the Bresenham algorithm in the context of rendering lines on screens. Furthermore, the article offers a practical dimension to this theoretical understanding by providing a comprehensive example of code written in JavaScript for generating an animation, also using HTML and CSS. This code example is designed to be easy to comprehend, even to those with limited programming experience, fostering the integration of animations into life science education. We synthesized findings from various studies to underscore the proven advantages of this new teaching tool, and by reviewing them, we reaffirm that animations have a demonstrable impact on improving the learning experience, making complex physiological processes more comprehensible and engaging. This highlights the critical role of animations as a pedagogical tool in science classrooms, and emphasizes the importance of understanding the mathematical and computational principles that support their creation. By bridging this knowledge gap, educators and students can make more effective and informed use of existing animation tools.